THE IMPLEMENTATION OF VISUAL AIDS IN HELLO ENGLISH APPLICATION FOR DEVELOPING VOCABULARY SKILLS JUNIOR HIGH SCHOOL STUDENTS - Dhoifatul Hasanah; Zainuddin; Beny Hamdani (LPPM Universitas PGRI Jombang, 2025)
This research seeks to examine the implementation of the use of visual aids in Hello English application in developing students' English vocabulary at SMP N 2 Gading. Visual aids, such as images, icons, and animations, function as interactive learning media that help students understand and remember vocabulary more effectively. This research employs a descriptive approach using a qualitative method. Data were obtained using observation, interviews, and questionnaires. Researchers use a qualitative approach because this approach primarily focuses on exploring the questions of why and how, and highlights comprehensive studies to uncover the truth. The entire process of this study shows that the use of visual aid-based applications not only makes students more focused and interested, but also creates a more enjoyable, effective, and involving learning experience for all parties. With an interactive atmosphere, students not only receive information, but also actively process and apply newly learned vocabulary